2015
DOI: 10.1186/s40064-015-1603-5
|View full text |Cite
|
Sign up to set email alerts
|

A phase I dose-escalation study of a biosimilar trastuzumab in Chinese metastasis breast cancer patients

Abstract: Trastuzumab has been widely used among the breast cancer patients with human epidermal growth factor receptor 2 (HER2) overexpression. The genetically engineered trastuzumab traded as Cipterbin® was developed in China since 2003. We have disclosed the phase I clinical trial data of safety, pharmacokinetic profile (PK) in patients with metastasis breast cancer. Subjects identified as HER2 strong positive received single intravenously doses of 100, 250 or 500 mg Cipterbin® in dose-escalation manner. The safety e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…DRL_TZ and RMP administered as a single 6 mg/kg intravenous dose were comparably well tolerated in the study population. The profile of drug-related events was similar to that observed in other TZ trials with frequently reported drug-related AEs being pyrexia, headache, chills and fatigue 16 27 29 . No new or unexpected safety events were observed.…”
Section: Discussionsupporting
confidence: 75%
“…DRL_TZ and RMP administered as a single 6 mg/kg intravenous dose were comparably well tolerated in the study population. The profile of drug-related events was similar to that observed in other TZ trials with frequently reported drug-related AEs being pyrexia, headache, chills and fatigue 16 27 29 . No new or unexpected safety events were observed.…”
Section: Discussionsupporting
confidence: 75%
“…Only one developed arrhythmia among the seven patients showing isotope uptake in myocardium on image [ 27 ]. In one small cohort including 27 metastatic BC patients, trastuzumab was believed to cause arrhythmias in 6 patients, one of which developed sinus bradycardia and others were unspecified [ 28 ]. In a larger study including 68,113 BC patients, the chemotherapy group was shown to have higher Af incidence, while in the subgroup analysis, there were no significant differences regarding trastuzumab use [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the study did not provide the maximum and minimum concentration, the median or mean +/− standard deviation, maximum or minimum is reported. The final set of reported studies are included in Table S1 (34, 7194).…”
Section: Methodsmentioning
confidence: 99%